Bangladesh HR professionals' competencies: Impact on firm performance and moderating effects of organisation life cycle. Issue 2 (6th August 2018) - Prikshat, Verma; Biswas, Kumar; Nankervis, Alan; Hoque, Md. Rakibul
Abstract : Purpose: The purpose of this paper is to examine the HR roles of Bangladesh HR professionals in the public and private firms in Bangladesh using Human Resource Competency Study (HRCS) model (2016). The impact of identified HR competencies on firm performance and moderation of this relationship concerning different stages of organisation life cycle (OLC) is also explored. Design/methodology/approach: This quantitative study uses the HRCS model (RBL, 2015) as its underpinning analytical framework, and explores the impact of identified HR competencies on firm performance and analyses whether this relationship is moderated by different OLC stages. The sample for this study consisted of 202 HR professionals from both public and private organisations in Bangladesh. Findings: Results confirmed that all the nine competencies of HRCS model were demonstrated by the HR professionals in Bangladesh. The "credible activist" competency achieved the top ranking and "paradox navigator competency" recorded the lowest. Minor variation in terms of levels of competencies was observed in the context of private and public firms. HR competencies positively impacted the firm performance and only the maturity and growth stages of a firm's life cycle moderated this relationship. Originality/value: There is a deficit of studies which have tested this relationship in terms of the moderating effects of OLC stages in the Asian developing country context. Focusing on this paucity of research concerning the transference of western human resource management models in developing economies and their resultant impact on firm performance, this is the first study set out to explore whether the most cited western HRCS model (RBL, 2015) is useful in understanding HR competencies in Bangladesh.